PURE LIVE SEED OF AGAPANTOS SEEDS AFTER CLASSIFICATION IN SEED BLOWER - PEREIRA, Gabriely Pinto; CARVALHO, Ruy Inacio Neiva de (Scientia Agraria, 2008)
The Agapanthus africanus is an ornamental specie of great use in Brazil. Its commercial multiplication is carried through vegetative propagation, however the plant produces many seeds that also can be used in its reproduction. The objective of this work was to evaluate the pure live seed of A. africanus seeds after classification in a seed blower aiming at its viability for propagation. The seeds were collected in Curitiba and analysed in the Laboratory of Technique of Seeds of PUCPR. The collected seeds were divided in six samples of 15 g. A sample was not blowed and the others were led to the seed blower regulated in five types of opening (1,5; 2,0; 2,5; 3,0; e 3,5). After 30 seconds, the part of the sample that was not taken by the air flow was submitted to the pureness analysis and the portion of pure seeds was submitted to the germination test on paper at 25 °C, using four replications of 100 seeds each. The germination was evaluated after 11 days. The benefit of the seeds separation was evaluated by the pure live seed of each sample. The increase of the draft increased the ratio of pure seeds of the sample and its capacity of germination. The seed blower was efficient in the separation increasing in up to 174,8% the pure live seed of the lot. The treatment in the opening of 3,5 provided germination of 84,3%, pureness of 93,3% and pure live seed of 78,6%.